Controversy in mining development: a study of the defensive strategies of a mining company. (2nd January 2020) - Karidio, Ismael; Talbot, David
ABSTRACT: This paper explores the neutralization techniques used by Strateco, a junior uranium mining company, throughout the development of the Matoush project in Quebec, Canada. Based on a content analysis of the company's annual reports, official company press releases, and newspaper articles, this study identifies six techniques used by the company to justify and defend its interests over the course of 10 years. The paper develops a better understanding of the defensive impression management strategies that resource-extraction companies may use to legitimize their positions and persuade concerned parties such as governments, stakeholders and right holders. The study contributes to the literature on neutralization techniques by documenting the employment and evolution of these techniques during controversies over resource extraction. It also highlights changes amongst concerned parties targeted by these techniques over the course of the conflict.